Human CD8 T lymphocytes recognize Mycobacterium tuberculosis antigens presented by HLA‐E during active tuberculosis and express type 2 cytokines. Issue 4 (17th February 2015) - Caccamo, Nadia; Pietra, Gabriella; Sullivan, Lucy C.; Brooks, Andrew G.; Prezzemolo, Teresa; La Manna, Marco P.; Di Liberto, Diana; Joosten, Simone A.; van Meijgaarden, Krista E.; Di Carlo, Paola; Titone, Lucina; Moretta, Lorenzo; et al.
<x xml:space="preserve">Abstract</x> CD8 T cells contribute to protective immunity against Mycobacterium tuberculosis. In humans, M. tuberculosis reactive CD8 T cells typically recognize peptides associated to classical MHC class Ia molecules, but little information is available on CD8 T cells recognizing M. tuberculosis Ags presented by nonclassical MHC class Ib molecules. We show here that CD8 T cells from tuberculosis (TB) patients recognize HLA‐E‐binding M. tuberculosis peptides in a CD3/TCR αβ mediated and CD8‐dependent manner, and represent an additional type of effector cells playing a role in immune response to M. tuberculosis during active infection. HLA‐E‐restricted recognition of M. tuberculosis peptides is detectable by a significant enhanced ex vivo frequency of tetramer‐specific circulating CD8 T cells during active TB. These CD8 T cells produce type 2 cytokines upon antigenic in vitro stimulation, help B cells for Ab production, and mediate limited TRAIL‐dependent cytolytic and microbicidal activity toward M. tuberculosis infected target cells. Our results, together with the finding that HLA‐E/M. tuberculosis peptide specific CD8 T cells are detected in TB patients with or without HIV coinfection, suggest that this is a new human T‐cell population that participates in immune response in TB.